COMMUNITY DEVELOPMENT TARGETS TO CHILDREN’S TIBAN MAS RESIDENCE IN UNDERSTANDING THE CONCEPT OF LEARNING AND PRACTICE PHYSICS THROUGH UTILIZATION OF INFORMATION TECHNOLOGY - Delia Meldra; Sestri Novia Rizki; Almandra Almandra; Yopy Mardiansyah (Universitas PGRI Sumatera Barat, 2021)
This activity aims to improve the understanding of the Tiban Mas children that physics or science subjects are not only memorized but with an understanding of concepts. This service activity is carried out with the stages of providing material but not directly formulating but followed by demonstration of practical tools and simple simulations on the material by utilizing developing technology. The basic principle is to directly invite the children of the Tiban Mas Residence to demonstrate the application of the physics concepts discussed. In addition, simulations are also shown that stimulate the children of the Tiban Mas Residence to be able to think that what they do every day is always related to physics or science. The technique used in this service activity is carried out in several ways including pretest, interview (focus group discussion), concept giving, through experimental studies (props and practicum), and post test. The results of the pretest showed the results of the means 53.83, after the service activities were carried out, it was continued with the posttest whether there was an increase in the value and the means obtained were 69.16. This service activity involves not only one scientific field but a combination of the fields of physics and engineering. The need for physical science is prioritized for understanding concepts. Meanwhile, engineering science focuses on the effectiveness of the design which includes assembling, installing and experimenting with props and simulations that will be made. This scientific amalgamation increases understanding which can be seen in the increase in posttest scores.